2017
DOI: 10.1371/journal.pone.0188978
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of patients with epilepsy and developmental delay using a customized panel of epilepsy genes

Abstract: Pediatric epilepsies are a group of disorders with a broad phenotypic spectrum that are associated with great genetic heterogeneity, thus making sequential single-gene testing an impractical basis for diagnostic strategy. The advent of next-generation sequencing has increased the success rate of epilepsy diagnosis, and targeted resequencing using genetic panels is the a most cost-effective choice. We report the results found in a group of 87 patients with epilepsy and developmental delay using targeted next ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 73 publications
7
49
0
Order By: Relevance
“…Our results were similar to previous reports, with diagnostic yields ranging between 10% and 48.5% [4956]. There were 60.5% (26/43) novel deleterious variants found in our study.…”
Section: Resultssupporting
confidence: 92%
“…Our results were similar to previous reports, with diagnostic yields ranging between 10% and 48.5% [4956]. There were 60.5% (26/43) novel deleterious variants found in our study.…”
Section: Resultssupporting
confidence: 92%
“…Epilepsy and intellectual disability (ID) are common neuropsychiatric disorders with an approximate prevalence of 0.3 to 2% . A subgroup of cases is due to pathogenic variants in potassium channels, which, however, might also present with a range of additional neurological features, such as ataxia .…”
Section: Introductionmentioning
confidence: 99%
“…To date, many studies have reported on the clinical utility of epilepsy gene panel testing. Although many custom-designed epilepsy gene panels produce similar lists of genes with pathogenic variants, there is substantial variability in their diagnostic rates, which range from 10 to 50% (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). This suggests that the diagnostic yield in these studies depends more on which patients are selected than on which custom-designed panel is used.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on early-onset epileptic encephalopathy patients, who may be at the severe end of the phenotypic spectrum (4,12). Recent epilepsy gene panel testing studies have analyzed large numbers of patients with broad epilepsy phenotypes (8,9,11,13,14). Since most studies report the results of referral-based tests, they include large variability in seizure onset, epilepsy type, familial occurrence, and the presence of development delay or encephalopathy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation